Kota Samarahan Pet Lost Using Location-Based Application - Rapheal, Andar (Universiti Malaysia Sarawak (UNIMAS), 2019)
Kota Samarahan Pet Lost is a mobile application that will help any pet owner to find their lost pet. Furthermore, this mobile application will let the users to post about any pet that they found near their area. Based on the studies that I had conducted, 100% of 27 respondents supported the objective of this project which is to develop a mobile application that will help users to post about their lost pet or any pet that they found near their area inside that application as well as to Facebook. Furthermore, geolocation will be applied in the development of this application as it allows the implementation of Global Positioning System (GPS). This mobile application will be developed in an android development. This project implementation will adopt the Waterfall Methodology. The main outcome of this location-based mobile application project is to help any pet owner to reunite with their lost pet and by helping to inform to the other pet owners about their lost pet that had been found nearby with a faster and efficient way possible. Hence, this mobile application will be most beneficial for the pet owner that really love their pet so much and wanted to reunite with their beloved lost pet as soon as possible with the help of their friends and the people that happens to be nearby their area at that moment.